A stretchable electrode for single enzymatic biofuel cells. (December 2021) - Li, Xin; Feng, Quan; Wu, Dingsheng; Mensah, Alfred; Li, Wei; Cai, Yibing; Li, Dawei; Wei, Qufu
Abstract: The rise of energy harvesting textiles opens up an emerging path to prospective energy solutions for the next generation of wearable electronics. Flexible electrodes as the core link in enzymatic biofuel cell (EBFC) should be stretchable while using enzyme molecules to transfer the energy from chemical of green fuels into electricity, which is beneficial to meet the key requirements of practical applications and shows considerable potential in wearable electronics. As a result, we develop a single EBFC based on intramolecular electron transfer using a stretchable electrode made of polyurethane/zeolitic imidazolate framework-8@laccase/carbon nanotubes (PU/ZIF-8@LAC/CNTs), which encapsulates LAC into ZIF-8 crystals during ZIF-8 in-situ growth on PU nanofibers. The maximal power density output of single-EBFC reached 1.33 W m −3 . More importantly, after multiple deformations of 75 stretching cycles, continuously stretching and holding and 180° twisting cycles, the single-EBFC retains an E OCV of more than 50%, which exhibits stable energy output, thus the stretchability of PU/ZIF-8@LAC/CNTs are proved. This stretchable electrode can establish a stable platform of power devices and will be potentially integrated into wearable electronics. Graphical abstract: Image 1 Highlights: Encapsulating enzyme into zeolitic imidazolate framework-8 during in-situ growth of zeolitic imidazolate framework-8 on polyurethane nanofibers. A single-enzymatic biofuel cell could decompose phenolic pollutants in the process of generating electricity. The single-enzymatic biofuel cell exhibited stable energy output while the stretchable electrode under repeated stretching and twisting cycles.